Religious Habitus of Neopentecostalists and Community Life - Nikolaevna Aleksandrova, Nadezhda (2021)
This article is devoted to one of the most active Christian movements - neo-Pentecostalism. To describe the functioning of neo-Pentecostal communities in Russia, the article uses the concept of "habitus" by P. Bourdieu, thanks to which it is possible to show the role of ministry practice in the everyday communal life and the religious everyday life of a believer. The concept of "religious habitus" in the article is understood as a system of stable dispositions, functioning as a structuring principle, generating and organizing practices and beliefs, thereby setting the daily routine of a religious community. The article also examines the neo-Pentecostal teaching about the "pentahedral" ministry, about the "gifts of the Holy Spirit" and the activities of the church, and the structural principles of a religious community functioning. It is shown that a believer, within the framework of socialization in the community, goes through the following stages: calling to service, professionalization, independent service, mentoring in service. Based on field research and presented narratives, it was revealed that the choice of religious service occurs according to the following types: on the recommendation of community leaders, arbitrary disclosure of the "Holy Spirit" gifts, by personal choice, and according to the rehabilitation type. The article raises the following question: can we talk about religious service as a religious practice or as a value-rational type of religious action?